AIDA (Attention, Interest, Desire, Action) as a Social Media Marketing Strategy towards Customer Loyalty of Pelakor Laundry Business. - Muhammad Izzatul Haq; Mohammad Adrian; Katty Cintiasari; Fernando Hosse Fahrezi; Mahrinasari MS (Journal Of Community Service for Economics and Business, 2025)
This study aims to explore the application of the AIDA model (Attention, Interest, Desire, Action) as a social media marketing strategy in enhancing customer loyalty at the "Pelakor" laundry business in Bandar Lampung. The research employs a qualitative descriptive approach with data collection techniques through in-depth interviews and focus group discussions (FGDs). The findings indicate that each stage of AIDA contributes positively to increasing consumer attention, interest, desire, and action, which in turn impacts satisfaction and loyalty. However, the study found that the business has not yet optimized the use of paid advertisements, loyalty programs, and a variety of digital payment methods. Recommendations are provided for the business to develop a digital-based loyalty program and expand payment channels to strengthen customer engagement.